Mapping cholera outbreaks and antibiotic resistant Vibrio cholerae in India: An assessment of existing data and a scoping review of the literature. (29th February 2020) - Chatterjee, Pranab; Kanungo, Suman; Bhattacharya, Sujit K.; Dutta, Shanta
Abstract: Although fluid and electrolyte replenishment remains the mainstay of clinical management of cholera, antibiotics are an important component of the strategy for clinical management of moderate to severe cases of cholera. The emergence of antibiotic resistance (ABR) in Vibrio cholerae has led to difficulties in case management. The past decade has also seen the development of cheap and effective oral cholera vaccines (OCVs). In addition to the two-dose strategy for widespread immunization, OCVs have also been shown to be effective in containing outbreaks using a single-dose schedule. In this scoping review we map the states and union territories (SUTs) of India which are prone to cholera outbreaks followed by a scoping review of peer-reviewed publications about ABR outbreaks of cholera employing the Arksey and O'Malley framework. Using the data reported by the Integrated Disease Surveillance Program (IDSP), we identified 559 outbreaks of cholera between 2009 and 2017, affecting 27 SUTs. We defined SUTs which had reported outbreaks in at least three out of the last five years (2012–2016) or had experienced two or more outbreaks in the same year in at least two of the last five years to be outbreak-prone. The scoping review identified 62 ABR outbreaks, with four SUTs accounting for two-thirds of them: West Bengal (14), Maharashtra (10), Odisha (10) and Delhi (7). Overall, this scoping review suggests that there is an increasing trend of ABR in Vibrio cholerae isolated from outbreaks in India. This opens up avenues for exploring the role of antibiotic stewardship in the clinical management of diarrhea, the institution of vaccination as an infection prevention intervention to reduce selection pressure, and the deployment of high quality surveillance systems which report accurate, real-time data allowing appropriate and timely public health responses. It is crucial to counter the issue of ABR in cholera before it assumes a menacing magnitude.